2014
DOI: 10.1007/s00464-014-4008-6
|View full text |Cite
|
Sign up to set email alerts
|

Long-term efficacy of transoral incisionless fundoplication with Esophyx (Tif 2.0) and factors affecting outcomes in GERD patients followed for up to 6 years: a prospective single-center study

Abstract: TIF by the EsophyX achieved lasting elimination of daily dependence on PPI in 75-80% of patients for up to 6 years. TIF seems an effective therapy for selected symptomatic GERD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(75 citation statements)
references
References 41 publications
3
70
0
2
Order By: Relevance
“…While we recognize that 11 patients were lost to follow-up for the 3-year evaluation, we believe that an attrition rate of 17 % is acceptable for any 3-year follow-up study. Additionally, as commonly seen in studies evaluating GERD therapies, not all patients were willing to undergo objective evaluation at the study intervals (Table 4); however, the consistent results between 1-, 2-, and 3-year follow-ups from this study, combined with the evidence from double-blind randomized studies [12, 13] and from the long-term European study [32], further support the safety, efficacy, and durability of TF. We conclude that TF offers chronic GERD patients with incomplete symptom control on PPI therapy an effective therapeutic alternative with lasting effect.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…While we recognize that 11 patients were lost to follow-up for the 3-year evaluation, we believe that an attrition rate of 17 % is acceptable for any 3-year follow-up study. Additionally, as commonly seen in studies evaluating GERD therapies, not all patients were willing to undergo objective evaluation at the study intervals (Table 4); however, the consistent results between 1-, 2-, and 3-year follow-ups from this study, combined with the evidence from double-blind randomized studies [12, 13] and from the long-term European study [32], further support the safety, efficacy, and durability of TF. We conclude that TF offers chronic GERD patients with incomplete symptom control on PPI therapy an effective therapeutic alternative with lasting effect.…”
Section: Discussionmentioning
confidence: 60%
“…Testoni et al [32] had reported that the percentage of patients who either stopped or halved their PPI therapy at 3-year follow-up was unchanged at 6 years (84 %), which portends positively for maintaining even longer-term PPI cessation rates in the same range. Interestingly, in the same study, complete discontinuation of PPIs dropped from 61 % of patients at 6 months to 30 % at 6 years, with the sharpest drop observed between 6 and 12 months post-TF, indicating that resumption of PPIs was most common within the first year after the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…48 Though the longest follow-up time is 22 months in PPINR, TIF has been shown to be effective in PPI responsive patients at 6 years. 65 Wendling et al reports a dysphagia rate of 0.5% with TIF which is dramatically lower than rates typically reported with LF or MSA; however, this data is all from observation studies rather than head-to-head comparisons. 40 Some investigators have argued TIF may be a valuable treatment for patients at higher risk of developing dysphagia due to esophageal dysmotility, though ineffective esophageal motility is an independent risk factor for TIF failure.…”
Section: Discussionmentioning
confidence: 83%
“…Preprocedure Hill's Grade I-II, hiatal hernia smaller than 2 cm, good esophageal motility, and numbers of fasteners were predictors of good clinical outcome [49]. If these factors are kept in mind TIF 2.0 can offer a powerful tool for symptomatic GERD patients.…”
Section: Endoscopic Antireflux Proceduresmentioning
confidence: 99%